Systematic Review of the Neurobiological Relevance of Chemokines to Psychiatric Disorders - Stuart, Michael J.; Singhal, Gaurav; Baune, Bernhard T. (Frontiers in Cellular Neuroscience, 2015)
Psychiatric disorders are highly prevalent and disabling conditions of increasing public health relevance. Much recent research has focused on the role of cytokines in the pathophysiology of psychiatric disorders; however the related family of immune proteins designated chemokines has been relatively neglected. Chemokines were originally identified as having chemotactic function on immune cells, however recent evidence has begun to elucidate novel, brain-specific functions of these proteins of relevance to the mechanisms of psychiatric disorders. A systematic review of both human and animal literature in the PubMed and Google Scholar databases was undertaken. After application of all inclusion and exclusion criteria, 157 references were remained for the review. Some early mechanistic evidence does associate select chemokines with the neurobiological processes, including neurogenesis, modulation of the neuroinflammatory response, regulation of the HPA axis, and modulation of neurotransmitter systems. This early evidence however does not clearly demonstrate any specificity for a certain psychiatric disorder, but is primarily relevant to mechanisms which are shared across disorders. Notable exceptions include CCL11 which has recently been shown to impair hippocampal function in aging - of distinct relevance to Alzheimer’s disease and depression in the elderly, and prenatal exposure to CXCL8 that may disrupt early neurodevelopmental periods predisposing to schizophrenia. Pro-inflammatory chemokines, such as CCL2, CCL7, CCL8, CCL12, CCL13, have been shown to drive chemotaxis of pro-inflammatory cells to the inflamed or injured CNS. Likewise, CX3CL has been implicated in promoting glial cells activation, proinflammatory cytokines secretion, expression of ICAM-1 and recruitment of CD4+ T-cells into the CNS during neuroinflammatory processes. With further translational research, chemokines may present novel diagnostic and/or therapeutic targets in psychiatric disorders.